EVALUASI PELAKSANAAN E-PROCUREMENT DI LINGKUNGAN KOTA TEGAL TAHUN 2010 - Rizki Anton Nugroho; Priyatno Harsasto; Nunik Retno H (Journal of Politic and Government Studies, 2013)
Procurement System in Tegal has implemented e-Procurement system. In the e-Procurement system of the whole process starting from the announcement of the auction, bidding, selection, until the announcement of the winner will be made online via the website (website). Internet access by the broader community, particularly in the construction business has made e-Procurement is flexibly applied and became a necessity for modern government. e-Procurement is believed to be an instrument for good governance and improved public services because it will increase cost efficiency, effectiveness, faster cycle times, improve government accountability. From the provider of construction services, the success in participating in the auction system soon is one of the factors determining survival.Of these problems can be answered with a descriptive qualitative research data collection techniques such as observation, interviews (interviews), and literature. Techniques of data analysis done by data reduction, organization and interpretation of data.This paper is the result of studies to recognize the characteristics of the implementation of e-Procurement program money is currently in the Department of Economic Development and Regional Secretary Tegal conclusions that can be drawn from this study regarding the implementation of an electronic auction system held in Government lingungan Tegal. Some problems were encountered, the recommendations can be delivered the lack of control of IT human resources, the availability of internet connections are limited. While the government is lack of human resources, There is improvement of the system that causes Audited interfere with the comfort of the e-Procurement system services to a standstill, most of the procurement committee still have not mastered the application of e-Procurement. And from the government's even harder training and development providers LPSE electronic goods, infrastructure improvements mainly problems of e-Procurement system is experiencing technical problems and technical center network.Keywords: e-Procurement, Manufacturers , Procurement of goods and services.